Quality assessment of packaged water brands in a university teaching hospital in southern Nigeria - Ekanem AM; Benson SA; Ekpuk IN; Amafaye WD; Akpan IE; Udo AI; Edem SA; David E; Akpabio KO; Nneamaka AA (Ibom Medical Journal)
Background: Every year, globally, high rates of morbidity and mortality from waterborne diseases are reported due to non-compliant packaged water that fails to meet recommended safety standards. While studies have assessed the quality of drinking water in communities, researches on water quality in healthcare facilities are scarce. Healthcare facilities must ensure safe drinking water sources, to prevent complicating patient illnesses or prolonged hospital stay.